Temperament and creativity – implications for mental health and education - Jaracz, Marcin (Journal of Education, Health and Sport, 2024)
Creativity is a complex phenomenon, which level is affected by variables such as intellectual competence, temperament, personality and emotions. Research shows that patients with bipolar affective disorder have a higher level of creativity than healthy controls. The model of affective temperament developed by Hagop Akiskal enables the research on relationships between predispositions to bipolar disorder and creativity. Previous studies on the relationship between affective temperament and creativity are conducted by comparing temperaments of representatives of creative professions and people outside this group, as well as by studying the relationship between affective temperament and creativity assessed both subjectively and through objective tests. However, the temperamental traits contributing to creative potential have their downside, as they have been linked to higher risk of psychological and emotional problems. They may also be related to poorer educational and academic achievement. The article presents up to date research on the relationship between affective temperament and creativity, as well as mechanisms explaining them. It also discusses the relationship between temperament, mental health, and educational achievement, as well as its implications for psychological and pedagogical interventions.